A questionnaire survey on radiation protection among 282 medical staff from 26 endoscopy‐fluoroscopy departments in Japan. Issue 1 (21st April 2021) - Hayashi, Shiro; Takenaka, Mamoru; Kogure, Hirofumi; Yakushijin, Takayuki; Maruyama, Hirotsugu; Hori, Yasuki; Yoshio, Toshiyuki; Ikezawa, Kenji; Takagi, Tadayuki; Asai, Satoshi; Matsunaga, Kazuhiro; Matsumoto, Kengo; et al.
Abstract: Background and aims: It is essential for endoscopists, technologists, and nurses to understand radiation protection. However, protective equipment usage is still low, and there is little awareness of radiation protection in practice. Methods: We conducted a questionnaire survey on radiation protection from January to February 2020. The participants were medical staff, including medical doctors, nurses, and radiological and endoscopy technician in endoscopy‐fluoroscopy departments. The questionnaire included 14 multiple‐choice questions divided among three parts: background, equipment, and knowledge. Results: We surveyed a total of 282 subjects from 26 institutions. There were 168 medical doctors (60%), 90 nurses (32%), and 24 technologists (9%). Although almost all staff members (99%) always wore a lead apron, only a few wore a thyroid collar (32%) and lead glasses (21%). The rate of wearing a radiation dosimeter was insufficient (69%), especially among doctors (52%). A few subjects knew the radiation exposure dose of each procedure (15%), and slightly over half had attended lectures on radiation protection (64%) and knew about the three principles of radiation protection (59%). Protection adherence did not differ by years of experience, knowledge of fluoroscopy, awareness of radiation exposure doses, or attendance at basic lectures on radiation protection. However, medical doctors who were aware of the radiation exposure dose of each procedure were significantly more likely to wear dosimeters than those who were not (p = 0.0008). Conclusion: Medical staff in endoscopy departments in Japan do not have enough radiation protection equipment or education.